Пріоритетні підходи до оцінки земельних активів у сільському господарстві - Жук, В.М.; Бездушна, Ю.С. (Економіка природокористування і сталий розвиток, 2020)
Визначено пріоритетні підходи і методологію здійснення справедливої (ринкової) оцінки вартості сільськогосподарських земель у фінансовій і статистичній звітності як чинника ціноутворення при її ринковому обігу та капіталізації в національному багатстві України. Узагальнено й охарактеризовано види оцінювання земель, які диференційовано відповідно до його мети, методології та призначення результатів. Обґрунтовано механізм запровадження системи галузевої облікової оцінки землі, що формується як галузевий портал і функціонує за умови нормативно-методичного забезпечення державних регуляторних інститутів з агрегацією найбільш ефективних методик оцінювання та статистичних баз даних. The publication focuses on prioritizing approaches to fair (market) valuation of agricultural land in financial and statistical reporting, as a factor in pricing its market turnover and capitalization in Ukraine's national wealth. Types of land valuation that are differentiated according to the purpose, methodology and purpose of the results are generalized. The procedure of soil boning, economic, regulatory and expert monetary evaluation of land plots is described. Priorities in approaches to land valuation for different purposes have been identified. It is concluded that the income approach, in particular the method of direct capitalization of rental income, is a priority in the assessment of agricultural land. Indicators for estimation of arable land by the method of capitalization of rent income, the procedure of their calculation of the source of information that we used in the process of testing these methodological approaches on a scale of Ukraine are generalized. A methodology for valuation of agricultural land for financial reporting purposes is proposed. The mechanism of introduction of the system of sectoral land valuation system, which is formed as an industry portal and functions under the regulatory and methodological support of state regulatory institutes with the aggregation of the available and most effective valuation methods and statistical databases, is substantiated. It is concluded that such a mechanism, with appropriate tools, will facilitate the capitalization of key domestic national wealth – agricultural land and provide for the possibility of price regulation of minimum and maximum prices when opening the relevant market. The priority approach to the assessment in this mechanism identified one that provides consideration of the value and market factor and the natural fertility and economic efficiency of the Ukrainian black earth.